1997
DOI: 10.1037/1040-3590.9.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of providing MMPI-2 test feedback to clients at a university counseling service: A collaborative approach.

Abstract: This study examined the therapeutic effects of sharing Minnesota Multiphasic Personality Inventory-2 (MMPI-2) assessment results with clients. It is based on an earlier study by S. E. Finn and M. E. Tbnsager (1992). Participants were 60 university students seeking psychological services from a university counseling service. All participants completed the MMPI-2 and several outcome measures. Within 2 weeks of completing the assessment, clients in the experimental group received test feedback, using a collaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
4
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 31 publications
9
112
4
5
Order By: Relevance
“…Finally, participants who reported having more positive feelings about the assessment experience were more likely to experience increases in self-esteem and decreases in symptomotology. Newman and Greenway (1997) replicated the first two findings from Finn and Tonsager's study in a sample of 60 Australian university students.…”
Section: Empirical Research On Collaborative and Therapeutic Assessmesupporting
confidence: 75%
See 3 more Smart Citations
“…Finally, participants who reported having more positive feelings about the assessment experience were more likely to experience increases in self-esteem and decreases in symptomotology. Newman and Greenway (1997) replicated the first two findings from Finn and Tonsager's study in a sample of 60 Australian university students.…”
Section: Empirical Research On Collaborative and Therapeutic Assessmesupporting
confidence: 75%
“…It was therefore hypothesized that the TA intervention would lead to increases in reported relationship satisfaction and decreases in reported disaffection and interpersonal conflict. In addition, results from preliminary studies have indicated TA may lead to greater psychological wellbeing (Finn & Tonsager, 1992;Newman & Greenway, 1997).…”
Section: Goals Of the Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…À partir d'un questionnaire d'évaluation, ils ont constaté que les indicateurs de détresse psychologique des participants s'étaient atténués lors du suivi deux semaines après la passation du questionnaire d'éva-luation clinique. Ces résultats ont été reproduits dans un contexte expérimental par Newman et Greenway (1997) qui ont clairement établi le lien entre les amé-liorations enregistrées et la rencontre de rétroaction de l'évaluation avec le clinicien. Les patients ayant été informés des résultats obtenus au test présentaient moins de détresse psychologique après la rencontre, ainsi qu'au moment du suivi après deux semaines.…”
Section: Discussionunclassified